Pemanfaatan Beras Merah dan Pisang Cavendish dalam Pembuatan Flakes Sebagai Isian Minuman Instan - Shinta Krisnamurti; Niken Purwidiani; Ila Huda P.D; Mauren Gita Miranti (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to develop flakes made from brown rice and cavendish bananas as instant drink fillings, with the aim of finding out: 1) the results of sensory tests of brown rice flakes and cavendish bananas as instant drink fillings which include color, shape, aroma, taste, texture, and preference level; 2) the nutritional content of brown rice flakes and cavendish bananas which include carbohydrates, fiber, vitamin B6, and proximate test include water and ash; and 3) the selling price of brown rice flakes and cavendish bananas as an instant drink filling of 25 grams/package. The research method used was experimental, with sensory quality assessment by 5 trained and 25 semi-trained panelists. Data analysis uses Anava Tunggal (one way anava). Nutritional content tests in the form of carbohydrates, fiber, vitamin B6 and proximate tests including water and ash were carried out by laboratory tests. Calculation of the selling price of 25 grams/package using conventional methods. The results of the study show that: 1) the criteria for the best product flakes formula with a ratio of 100:60 produced a reddish-brown color, neat round shape, typical banana aroma, sweet taste, crispy texture and liked by the panelists; 2) the nutritional content per 100 grams of brown rice flakes and cavendish bananas has a total carbohydrate content of 71.06%, fiber 3.11, vitamin B6 2.66, moisture content 0.12% and ash content 0.11%; and 3) the selling price of flakes is known to be Rp. 7,290 per package weighing 25 grams.